2017
DOI: 10.1002/jpln.201700052
|View full text |Cite
|
Sign up to set email alerts
|

Linking sorghum nutrition and production with arbuscular mycorrhizal fungi and alternative soil amendments

Abstract: Mounting fertilizer costs are disproportionally affecting farmers in developing countries. Alternative soil fertility amendments [worm compost, pyrolyzed carbon (biochar)] and arbuscular mycorrhizal fungi have the potential to reduce these costs while promoting soil health. Our greenhouse study investigated the role of mycorrhizal associations and alternative fertility amendments on the productivity and plant nutrition of grain sorghum. We assessed sorghum (Sorghum bicolor cv. Macia) grown with ten different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Our previous research with sorghum ( Sorghum bicolor ) showed similar improvements in plant tissue mineral contents, particularly P, for plants amended with reduced commercial fertilizer rates + biochar + worm compost; however, root colonization was also ∼60% greater for those plants ( Cobb et al., 2018 ). While root colonization does not always indicate improved nutrient uptake ( Klironomos, 2003 ), it is often correlated, such that greater colonization tends to improve plant nutrient uptake ( Treseder, 2013 ; Cobb et al., 2016 ).…”
Section: Discussionmentioning
confidence: 73%
“…Our previous research with sorghum ( Sorghum bicolor ) showed similar improvements in plant tissue mineral contents, particularly P, for plants amended with reduced commercial fertilizer rates + biochar + worm compost; however, root colonization was also ∼60% greater for those plants ( Cobb et al., 2018 ). While root colonization does not always indicate improved nutrient uptake ( Klironomos, 2003 ), it is often correlated, such that greater colonization tends to improve plant nutrient uptake ( Treseder, 2013 ; Cobb et al., 2016 ).…”
Section: Discussionmentioning
confidence: 73%
“…Selective breeding for improved host‐plant partnership with mycorrhizal fungi is a necessary step, setting the stage for additional efforts to use soil amendments and agroecosystem management to support effective microbial symbioses (Cobb, Wilson, & Goad, 2018; Cobb, Wilson, Goad, & Grusak, 2018; Duhamel & Vanderkoornhuyse, 2013; Smith et al., 1992). Mycorrhizal symbioses are widespread and typically beneficial, suggesting that evaluation of mycorrhizal relationships is critical groundwork for disentangling additional plant‐associated microbial dynamics of the total holobiont.…”
Section: Introductionmentioning
confidence: 99%